High Interleukin-6 Level Increases Depression Risk on Geriatric Population in Denpasar, Bali-Indonesia - Purnamasidhi, Cokorda Agung Wahyu; Kuswardhani, R.A. Tuty (BALI MEDICAL JOURNAL, 2016)
Background: High interleukin-6 (IL-6) serum level was responsible in inflammatory regulation through the interaction within macrophage, glial melatonin production and regulation of methyl CpG- binding protein 2 (MeCP2) and influenced neuro-inflammation process, thus, it increased the risk of depression. The aim of this study was to determine whether high interleukin-6 serum level increased the risk of depression in geriatrics. Methods: A case control was performed as the design of this study. Geriatric populations with depression enrolled as the case group and without depression as control group. Assessment of IL-6 serum level was conducted by the patient’s venous blood. The IL-6 serum> 10 pg/ml was categorized as high. Results: In this study, 30 cases and 30 controls who met the criteria included as samples. There were 20 males (66.7%) and 10 females (33.3%). Factors associated with an increased risk of depression in geriatric were a high level of serum interleukin-6 (OR=3.60; CI95%: 1.22-10.64, p=0.018) and a marital status (OR=3.50; CI95%: 1.11- 1.02, p=0.028). High level of interleukin-6 was a significant and an independent risk factor of depression in geriatric (OR=3.60; CI95%: 1.22-10.64, p=0.021) in multivariate analysis. Conclusion: This study concluded that high IL- 6 serum level increased the risk of depression in geriatric.